Students’ Integrated Science Process Skills and Argumentation in Basic Natural Science Lecture - Findiyani Ernawati Asih; Dian Novita; Ivan Ashif Ardhana (Universitas Pendidikan Ganesha, 2022)
Rapid technological developments allow social studies students to practice i-SPS through practicum methods. This study aims to analyze the integrated science process skills (i-SPS) and the arguments of social studies students. i-SPS through demonstration methods and virtual experiments using pHET simulations, while arguments through debate activities involving the pro group (pseudoscience view) and the contra group (scientific view). The design of this research is a mixed method. The qualitative aspect analyses the i-SPS learning achievement of social studies students who use the rotating learning method. In contrast, the quantitative aspect is the correlation test between the i-SPS with pHET and argumentation. The mean score of i-SPS based on pHET is 83.46, i-SPS based on the demonstration is 55, while the average argumentation score is 77.88. The results of the nonparametric correlation test obtained that rcount 0.175 is more minor than rtable 0.404. So there is no correlation between i-SPS with pHET and argumentation. About 75% of social studies students have the i-SPS combination category, which is not balanced according to pHET and arguments. I-SPS-PHET students do not affect their arguments. Several factors can influence the argumentation of social students, such as experiences about phenomena, information in the digital era, and the characteristics of debates involving extended groups of pros and cons.